Does Religiosity Affect Attitudes toward the Ethics of Tax Evasion? The Case of Turkey - McGee, Robert W. (Religions, 2020)
This study surveys the opinion of a wide segment of Turkish society on the ethics of tax evasion. The survey instrument includes 18 statements used to justify tax evasion in the past. The research also finds that some reasons to justify tax evasion proved more attractive to participants than others. In our survey, the strongest support for tax evasion was in cases where the government abused human rights, where the government was corrupt or wasted tax funds, or where the taxpayer did not benefit from the tax expenditures. Conversely, the weakest arguments were in cases where the taxpayer did benefit from the tax expenditures or where the tax funds were spent wisely. What separates this study from others on the ethics of tax evasion is that it addresses interpersonal and intrapersonal religiosity. Its finding confirms the existence of an important relationship between both interpersonal and intrapersonal religiosity and the view toward the ethics of tax evasion.